Corporate governance, board diversity and bank efficiency: The case of commercial banks in Malaysia - Chan, S.G.; Lee, T.H. (2010)
The subprime crisis in the mid-2008 has resulted in failure of major financial institutions in many countries. Kirkpatrick (2009) pointed out that such problems were primarily due to information asymmetry in the banking industry where information about the banks’ exposure failed to reach the board and senior management. Therefore, good corporate governance practices are crucial for long-term survival of banking industry. The study examines the effect of board size and board composition on cost and profit efficiency of the commercial banks in Malaysia from 2000 to 2009 by employing Data Envelopment Analysis (DEA). Next, the Tobit regression is utilized to determine the effect of board composition and board size on cost and profit efficiency by controlling for liquidity risk, bank size, non-performing loans ratio, return to equity, and ratio of equity to total assets. Results found that independent director is positively related to cost efficiency. This implies that independent directors provide an effective monitoring role in over sighting and evaluating the performance of management in the banking industry. The results of the present study suggested that board size does not influence cost and profit efficiency of the commercial banks in Malaysia. This is consistent with the studies by Adams and Mehran (2008) and Zulkafli and Samad (2007). Gender diversity is also found to have no significant effect on cost and profit efficiency of the commercial banks in Malaysia. This is likely due to the relatively lower percentage of female in the corporate boardroom.